Pengaruh Perang Rusia dan Ukraina Terhadap Perekonomian Negara Kawasan Asia Tenggara - Donna Jesika Gulo; Dina Miranda Tarihoran; Putri Yohana Damanik; Amanda Riniaty; Sri Hadiningrum (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The war between Ukraine and Russia has had a big influence on the world, especially from a political perspective. Russia's invasion of Ukraine on Thursday, February 24 2022 stems from internal conflict between the two countries. Due to this incident, Russia received criticism from the international community, including Indonesia. The United States condemned the invasion and imposed economic sanctions on Russia. These sanctions take the form of stopping the operations of Russian-owned financial institutions in the United States, freezing all investment assets and property of individuals close to the Russian President, as well as restrictions on Russian debt transactions. After being hit by economic sanctions, Russia was also subject to a crude oil embargo by the European Union and the United States. The war that occurred influenced the increase in oil prices due to Russia's invasion of Ukraine, causing new challenges in the global economy. This research uses library research. Library research is research whose main object is literature (library) which utilizes sources from literature to obtain research data, so that library research limits its activities to literary materials related to the research object. The research results show that the war between Russia and Ukraine has had various negative impacts that threaten all sectors, especially the economy in terms of global trade. As is known, these two countries are the largest suppliers of various main commodities such as wheat, fertilizer, natural gas and oil. Where these commodities are really needed by international consumers. Russia and Ukraine have a significant market share of the supply of oil, gas and other commodities, so the invasion has increased the prices of these commodities. The direct impact of rising commodity prices affects economic growth in the countries involved. This means that the economy in Southeast Asia will be affected by the war that is taking place. Continued conflict could have drastic effects in Southeast Asia. The impact of the Russian and Ukrainian wars has an impact on the Southeast Asian economy and will be more detrimental than the impact of the COVID 19 pandemic. This is because it is related to the global economy in essential areas.